Canis familiaris (carnívora: Canidae) como sentinelas da saúde animal e humana no Parque Estadual do Ibitipoca e entorno, município de Lima Duarte MG, Brasil. - Julio Cesar Rocha Costa (2011)
The presence of domestic dogs in conservations units (protected areas) is quite a common reality in Brazil. It is considered a serious problem which is hard to solve and mainly caused by the abandonment or neglect of dogs by their owners. This behavior can cause serious environmental problems, such as the interference of these domestic animals in several aspects regarding the survival of populations of wild animals and ecological stability of ecosystems. Additionally, stray and/or feral dogs may carry several pathogens or pathogen vectors, related to zoonotic diseases. Therefore, it is important and necessary to study these animals in areas located close to protected nature reserves which are frequently visited by the general public. The Ibitipoca State Park is located in the Zona da Mata Mineira, between the municipalities of Lima Duarte and Santa Rita do Ibitipoca. Situated in one branch of the Mantiqueira mountain range and inserted in the Atlantic forest biome, it is considered the most visited park of the state of Minas Gerais, attracting on average over 30.000 visitors per year. The aim of this study was to identify parasites and other pathogens in stray dogs around the Ibitipoca State Park, in order to evaluate the possibility of their transmission to wild canids in the Park and the risk they repreent to public health. To this will be presented in the chapters that follow studies involving: the profile of the dogs sampled and popular knowledge about local problems stray dogs and / or feral, hematologic and biochemical profile of these dogs, and the occurrence of Leishmania sp. hemoparasites, intestinal parasites, ectoparasites, bacteria and viruses in these animals. From September 2008 to August 2009, of blood samples, feces and ectoparasites were collected from 110 stray dogs, 80 males and 30 females, distributed among 51 properties located near the vicinity of Ibitipoca State Park. Inside the park, trails were also visited on several occasions, in a non systematic way, aiming at finding and collecting fresh feces of wild and domestic canids. The sites of all fecal samples collected, as well as the sites for the collection of biological material of the dogs sampled, were spatially marked with the aid of GPS. Questionnaire - based interviews were also conducted with the animal owners and other residents around the Park. The vast majority of animals examined are not vaccinated against viruses nor dewormed by their owners. Typically the dogs in the region are either companion or guard dogs, or farm or hunting dogs. However, many animals, according to residents, have no use at all. Among the dogs hematologically examined, the primary findings were the presence of many segmented leukocytes and eosinophilia. In biochemical analysis the main changes found were hypoalbuminemia, hypergammaglobulinemia and hyperproteinemia. Of the 110 dogs examined, 39 (35.45%) were seropositive for Ehrlichia canis, 29 (26.36%) for Babesia canis, 40 (37.03%) for Rickettsia rickettsii and 25 (22.72%) for the presence of Leishmania sp., based on the molecular and serological tests applied. In the enteroparasitological study the proportions of positive faecal samples of C. brachyurus and Canis familiaris, obtained within the national park, were respectively 79.31% and 60%. Of the 83 animals examined in the Park, 49 (59.03%) were positive for a parasite and/ or helminth. At least 13 morphotypes of intestinal parasites were found in the study area, and seven were found in both dogs and guará- wolves. Five of the 13 morphotypes have zoonotic potential: Sarcocystis spp., Ancylostomatideo, Dipylidium caninum, Toxocara spp. e Giardia spp. A total of 1,469 ectoparasites belonging to 13 species of the Siphonaptera, Ixodes and Phitiraptera orders were collected from the animals. Besides these, the presence of two species of dipterous parasites were also reported, but not quantified. In virology, among the dogs examined, 92.15% presented positive serology for canine parvovirus, 50% for the distemper virus, 14.85%, for the canine corona virus (CCV) 61.76% for the canine adenovirus type 2 and 92.07% for the canine parainfluenza virus. Areas shared by domestic and wild dogs were determined based on the location and collection of fecal samples within the park. The most likely overlapping area is the one situated in the sub-region known as the way up to mata grande. The possibility of infection by domestic dogs, wild animals, residents and tourists in the region actually exists, which demonstrates the importance of using Canis familiaris wandering and / or feral as sentinels of human health, animal and wild, especially when placed next to natural areas. Measures of prevention and control of these animals should be implemented to reduce its impact on biodiversity and human health